“Hot Septum” Sign of Constrictive Pericarditis - Edgar Argulian, MD MPH; Dan G. Halpern, MD (JACC: Case Reports, 2020)
In patients with constrictive pericarditis, a characteristic reduction in the regional longitudinal strain seen in the areas of the left ventricular free wall and relative sparing of the septal longitudinal strain values create an easily recognizable bullseye plot pattern that can be described as “hot septum.” (Level of Difficulty: Beginner.)